Microbial biosorption of metal in effluent miners - Orduz, Francisco; Chaves, Aura Leticia (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2008)
The mining is essential inside the energetic development of a country, but also it is one of the activities that affect the environment and the quality of life of the peoplewho live in the mining zones. The technology of bioremediation is based on the use of microorganisms which degrade and tranform pollutant subtances in terrestrial and aquatic ecosystems. The aim of this work was the design of an integrated physicochemical and biologicalsystem for diminishing the concentration of iron of the effluent miners by using technologies of biosorption microbial, which is formed by bioreactor and a fungus biomass for studying the efficiency of the decontamination of mine acid drainages (MAD) with heavy metals, specially the derivatives of the oxidation of the pyrite (iron). In this work were used four genus Aspergillus gfungus species and four genus Rhizopus fungus species, all these were alive and inert; besides two kind of bioreactors of fixed bed and fluidized bed and different times of residence of the water in the systemof the biofiltration were used. The elimination of iron (was of the 95.2%) was more effective in the systems of biofiltration where was employed a bioreactor f fixed bed with inert fungus biomass, with time of residence between twenty and forty minutes. In relation with the decrease of the water acidity, the PH value increased when the concentration of iron diminished.